CORR(®) ORS Richard A. Brand Award for Outstanding Orthopaedic Research: Engineering Flexor Tendon Repair With Lubricant, Cells, and Cytokines in a Canine Model - Zhao, Chunfeng (Springer US, 2014)
BACKGROUND: Adhesions and poor healing are complications of flexor tendon repair. QUESTIONS/PURPOSES: The purpose of this study was to investigate a tissue engineering approach to improve functional outcomes after flexor tendon repair in a canine model. METHODS: Flexor digitorum profundus tendons were lacerated and repaired in 60 dogs that were followed for 10, 21, or 42 days. One randomly selected repair from either the second or fifth digit in one paw in each dog was treated with carbodiimide-derivatized hyaluronic acid, gelatin, and lubricin plus autologous bone marrow stromal cells stimulated with growth and differentiation factor 5; control repair tendons were not treated. Digits were analyzed by adhesion score, work of flexion, tendon-pulley friction, failure force, and histology. RESULTS: In the control group, 35 of 52 control tendons had adhesions, whereas 19 of 49 treated tendons had adhesions. The number of repaired tendons with adhesions in the control group was greater than the number in the treated group at all three times (p = 0.005). The normalized work of flexion in treated tendons was 0.28 (± 0.08), 0.29 (± 0.19), and 0.32 (± 0.22) N/mm/° at Day 10, Day 21, and Day 42 respectively, compared with the untreated tendons of 0.46 (± 0.19) at Day 10 (effect size, 1.5; p = 0.01), 0.77 (± 0.49) at Day 21 (effect size, 1.4; p < 0.001), and 1.17 (± 0.82) N/mm/° at Day 42 (effect size, 1.6; p < 0.001). The friction data were comparable to the work of flexion data at all times. The repaired tendon failure force in the untreated group at 42 days was 70.2 N (± 8.77), which was greater than the treated tendons 44.7 N (± 8.53) (effect size, 1.9; p < 0.001). Histologically, treated repairs had a smooth surface with intrinsic healing, whereas control repairs had surface adhesions and extrinsic healing. CONCLUSIONS: Our study provides evidence that tissue engineering coupled with restoration of tendon gliding can improve the quality of tendon healing in a large animal in vivo model. CLINICAL RELEVANCE: Tissue engineering may enhance intrinsic tendon healing and thus improve the functional outcomes of flexor tendon repair.